Evaluation of The Quality of Work of The Ministry of Religious Affairs of Solok City Employees Influenced by Work Discipline, Employee Development, and Organizational Culture - Rasidah Nasrah; Muhammad Rahul; Wahyu Indah Mursalini (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
An employee, or a group of employees, is required to have high productivity when carrying out their work or completing tasks. Essentially, productivity doesn't just focus on generating a large amount of work but also considers the final product's quality. This study aims to determine the effect of work discipline, employee development, and organizational culture on the quality of work of employees of the Ministry of Religion of Solok City. This study uses a quantitative approach and primary data. This study utilized a sample of 43 employees from the Ministry of Religion in Solok City. This study employed the complete sampling method. The data analysis techniques employed in this study include validity tests, reliability tests, multiple linear analyses, and coefficient of determination (R2). The study's results suggest that work discipline significantly influences the quality of work produced by employees at the Ministry of Religion in Solok City. Religion of Solok City. Organizational culture does not significantly influence the quality of work performed by employees of the Ministry of Religion in Solok City. Employee development and organizational culture have a significant effect on the quality of work of employees of the Ministry of Religion of Solok City. The R square of 22% reveals the coefficient of determination (R2), indicating a low degree of closeness between the dependent and independent variables. Other variables outside the model discussed in this study, like communication, training, coaching, and others, influence the remaining 78%.